ANALISIS SUPERVISI KEPERAWATAN DENGAN PELAKSANAAN BUDAYA SAFETY DIRUMAH SAKIT UMUM DAERAH dr. H. ISHAK UMARELLA - Dewi Arwini Bugis; Harianti Bugis (STIKES Pasapua Ambon, 2022)
Introduction: Supervision is one of the factors that influence nurse compliance in carrying out their duties at the hospital. Implementing nurses who carry out their duties properly will create good and quality nursing services so that they can ensure patient safety during treatment. Purpose: to find out the relationship between nursing supervision and the implementation of a safety culture at the Regional General Hospital dr. H. Ishak Umarella. Methode: Quantitative descriptive with cross sectional. The population and sample in this study were all nurses who had STR in the inpatient room of the Regional General Hospital dr. H. Ishak Umarella numbered 70 people using total sampling. Testing using the Chi-Square test. Results: Implementation of nursing supervision at the Regional General Hospital dr. H. Ishak Umarella found that most of the respondents were in the good category and 35 respondents (50%) were in the poor category. Safety culture at the Regional General Hospital dr. Most of H. Ishak Umarella was in good category with 54 respondents (77.1%). The results of the Chi-Square test obtained the Fisher’s Exact Test value obtained a significance value of 0.01 (ρ = 0.01 <0.05). Conclusion: There is a relationship between nursing supervision and the implementation of a safety culture at the Regional General Hospital dr. H. Ishak Umarella. Suggestion: The Hospital provides rewards in the form of support and motivation to each nursing service unit that successfully implements and improves safety culture